Emerging and reemerging aedes-transmitted arbovirus infections in the region of the americas: implications for health policy - Espinal, Marcos A.; Horstick, Olaf (American journal of public health, 2019)
The increasing geographical spread and disease incidence of arboviral infections are among the greatest public health concerns in the Americas. The region has observed an increasing trend in dengue incidence in the last decades, evolving from low to hyperendemicity. Yellow fever incidence has also intensified in this period, expanding from sylvatic-restricted activity to urban outbreaks. Chikungunya started spreading pandemically in 2005 at an unprecedented pace, reaching the Americas in 2013. The following year, Zika also emerged in the region with an explosive outbreak, carrying devastating congenital abnormalities and neurologic disorders and becoming one of the greatest global health crises in years.The inadequate arbovirus surveillance in the region and the lack of serologic tests to differentiate among viruses poses substantial challenges. The evidence for vector control interventions remains weak. Clinical management remains the mainstay of arboviral disease control. Currently, only yellow fever and dengue vaccines are licensed in the Americas, with several candidate vaccines in clinical trials.The Global Arbovirus Group of Experts provides in this article an overview of progress, challenges, and recommendations on arboviral prevention and control for countries of the Americas.
Gesehen am 18.09.2019